2016
DOI: 10.3748/wjg.v22.i1.253
|View full text |Cite
|
Sign up to set email alerts
|

Current status and perspectives of immune-based therapies for hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a frequent cancer with a high mortality. For early stage cancer there are potentially curative treatments including local ablation, resection and liver transplantation. However, for more advanced stage disease, there is no optimal treatment available. Even in the case of a "curative" treatment, recurrence or development of a new cancer in the precancerous liver is common. Thus, there is an urgent need for novel and effective (adjuvant) therapies to treat HCC and to prevent rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 69 publications
0
35
0
1
Order By: Relevance
“…It has been reported that cellular immunotherapy could strengthen the immune state and afford a potential value in enhancing the therapeutic outcome [13], although it has not been considered as a standard therapy for HCC. Several studies and meta-analysis had revealed that the combination of cellular immunotherapy of conventional therapies was more effective [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that cellular immunotherapy could strengthen the immune state and afford a potential value in enhancing the therapeutic outcome [13], although it has not been considered as a standard therapy for HCC. Several studies and meta-analysis had revealed that the combination of cellular immunotherapy of conventional therapies was more effective [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Один из возможных механизмов противоопухолевого эффекта интервенци-онного воздействия -иммунокомпетентная гибель опу-холевой клетки [12]. Локальный некроз и гибель опухоле-вых клеток приводят к неспецифической (высвобожде-ние большого количества «сигналов опасности» или т.н.…”
Section: таргетная терапия опухолейunclassified
“…This may hampers an effective immune response against cancer cells[78]. Moreover this is a challenge on the use of conventional immunotherapy is challenged.…”
Section: Exploring the Etiopathogenesismentioning
confidence: 99%